1947
DOI: 10.1038/bjc.1947.21
|View full text |Cite
|
Sign up to set email alerts
|

Forced Activation and Early Detection of the Milk-borne Agent of Mammary Adenomas in Mice

Abstract: THE presence and activity of the milk-borne agent of mammary tumours of mice discovered by Bittner (1936) are detectable only by the growth of a mammary tumour. No other criterion of its presence is yet generally accepted, though an opinion is widely held that certain localized nodular adenomatous mammary hyperplasias are an expression of the combined activity of the milk-borne tumour agent and a mammogenic hormone. Focal or nodular adenomatous hyperplasias in the mammae of dealer's mice were first described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1949
1949
1975
1975

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Richardson (67) reported complete regression of stilbestrol‐induced acinar changes in male rats after the drug was discontinued. This confirmed prior studies by Fullinger (63), who found complete involution of the induced breast changes in male mice within twenty‐four to twenty‐eight weeks after cessation of therapy. A true malignant lesion, regardless of the type of etiologic influence, must endure after cessation of that influence.…”
Section: Action Of Estrogen In Other Speciessupporting
confidence: 90%
See 1 more Smart Citation
“…Richardson (67) reported complete regression of stilbestrol‐induced acinar changes in male rats after the drug was discontinued. This confirmed prior studies by Fullinger (63), who found complete involution of the induced breast changes in male mice within twenty‐four to twenty‐eight weeks after cessation of therapy. A true malignant lesion, regardless of the type of etiologic influence, must endure after cessation of that influence.…”
Section: Action Of Estrogen In Other Speciessupporting
confidence: 90%
“…The effect of estrogen therapy as a carcinogenic agent is also a question of great importance. It seemed pertinent, therefore, to review the literature on the subject (1–75), and to add the following case report…”
mentioning
confidence: 99%
“…The R III X were bred by subsequent litter mating from one R III female and one male of the same litter which had been cross-suckled on a nursing C57 black mother in 1944 (Pullinger, 1947). In 228 breeders of this subline freed from the Bittner agent, the following spontaneous tumours have occurred: one mixed squamous and adenocarcinoma at 23 months old in a breeder spayed at 20 months; one unmixed squamous-celled carcinoma of mammary gland at 22 months in a mouse spayed at 20 months; one unmixed adenocarcinoma of the mammary gland at 19 months old in an intact animal; two sarcomas at 7 and 14 months old respectively; many lymphomas; many pulmonary adenomas and one carcinoma; one papilloma of the skin.…”
Section: Methodsmentioning
confidence: 99%
“…The mice here described had to be killed on account of large skin turnours, despite attempts to avoid them, before any mammary tumours had arisen. Early effects of methylcholanthrene on mammary epithelium were, nevertheless, sought for in accordance with a previous plan to determine the first morphological changes in cells that might be attributed to carcinogenic agents (Pullinger, 1940). It happened that in these young breeders foci of squamous differentiation exactly similar to those in the old untreated females were found but three times as often as in untreated mice and in greater numbers per mammary gland (Table III).…”
mentioning
confidence: 96%